Italian and international property valuation methods: A critical comparison - Murro, Rocco (Edelweiss Applied Science and Technology, 2025)
The article aims to outline the main features of the property valuation methodologies of the Italian tradition and to make a critical comparison with international procedures in order to indicate a possible path for the implementation of Italian property valuation standards. The study has been structured as follows: after an introductory overview in which the current needs and challenges of property valuation in the international context have been outlined, the characteristics of the Italian and international valuation methodologies are illustrated; then, a critical comparison has been proposed and the main results of this comparison have been discussed; finally, concluding remarks have been provided. The comparison of the Italian appraisal tradition with international methodologies showed strong analogies between the Italian practice and the international one, especially in terms of consistency with the theoretical and methodological principles of property appraisal; therefore, the need to align the Italian valuation practice with the needs emerging from the real estate market cannot mean the denial of the local valuation tradition. This study can represent a starting point for the definition of property valuation standards based also on the local valuation practice, by means of a bottom-up process involving all the representatives of the property valuation sector.